Linking foraging behaviour of post-breeding adult female elephant seals from Marion Island to physical dynamics and productivity at the South-West Indian Ridge - Biermann, Lauren (Department of Oceanography, 2014)
Advances in remote sensing and tagging technology have made it possible to investigate the relationship between oceanographic dynamics and the distribution of certain marine species. For this study, surface chlorophyII-a concentration was used as a proxy for underlying related productivity, rather than as a direct indicator of prey density. Post-breeding, adult female southern elephant seals from Marion Island were tagged with conductivity, temperature and depth satellite-relayed data loggers (CTD-SRDL's) and their foraging behaviour was examined in relation to different chlorophyII-a concentrations. Optimal foraging and area restricted search theories predict that travelling speed and turning frequency would be quantifiably affected by prey density, which is in turn affected by the underlying richness of primary producers.